Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Phenotypically Wild Barley Shows Evidence of Introgression From Domesticated Barley - Chaochih Liu; Li Lei; Mingqin Shao; Jerome D. Franckowiak; Jacob B. Pacheco; Jeness C. Scott; Ryan T. Gavin; Joy K. Roy; Ahmad H. Sallam; Brian J. Steffenson; Peter L. Morrell (Molecular Ecology, 2026)
Multiple studies have reported genetic evidence of crop‐to‐wild introgression in phenotypically wild accessions of wild barley ( Hordeum vulgare ssp. spontaneum ). We examined 318 Wild Barley Diversity Collection (WBDC) accessions for evidence of introgression from domesticated barley. Using SNP genotyping data, we performed local ancestry inference between the WBDC accessions and domesticated barley to identify genomic regions with evidence of introgression. Using the genomic intervals for well‐characterised genes involved in domestication and improvement, we examined the evidence for introgression at genomic regions potentially important for maintaining a wild phenotype. Our analysis revealed that nearly 16% (48 of 318) of WBDC accessions showed evidence of introgression from domesticated barley, with up to 16.6% of the genome introgressed. All accessions identified as introgressed based on domestication‐related phenotypes show clear genetic evidence of introgression. The size of runs of identity by state and local ancestry inference suggests that most introgression did not occur recently. This study suggests a long history of genetic exchange between wild and domesticated barley, highlighting the potential for introgression to influence the genetic makeup and future adaptation of wild populations, with implications for plant conservation strategies.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Use of a sperm-Hyaluronan binding assay for evaluation of sperm quality in dromedary camels - A. Kotila-Ioannou; JM Morrell; T. Ntallaris; M. Gargallo; J.A. Skidmore; C. Malo (Animal Reproduction Science, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Echocardiographic characterization of age- and sex-associated differences in cardiac function and morphometry in nonhuman primates - Maria Cristina Florio; Laura Fusini; Gloria Tamborini; Christopher Morrell; Alise McDonald; Michelle Walcott; Kenneth Ridley; Kelli L. Vaughan; Julie A. Mattison; Mauro Pepi; Edward G. Lakatta; Maurizio C. Capogrossi (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Transplacental infection by bovine alphaherpesvirus type 1 induces protein expression of COX-2, iNOS and inflammatory cytokines in fetal lungs and placentas - Mercedes M. Burucúa; María A. Risalde; Felipe A. Cheuquepán; Silvina Quintana; Sandra E. Pérez; Germán J. Cantón; Dadin P. Moore; Anselmo C. Odeón; Irene Agulló-Ros; María Valeria Scioli; Claudio Barbeito; Eleonora L. Morrell; et al. (Veterinary Microbiology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Low-density colloid centrifugation removes bacteria from boar semen doses after spiking with selected species - E. Lacalle; S. Martínez-Martínez; E. Fernández-Alegre; C. Soriano-Úbeda; J.M. Morrell; F. Martínez-Pastor (Research in Veterinary Science, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Longitudinal uncoupling of the heart and arteries with aging in a community-dwelling population - Majd AlGhatrif; Chris H. Morrell; Lewis C. Becker; Paul D. Chantler; Samer S. Najjar; Luigi Ferrucci; Gary Gerstenblith; Edward G. Lakatta (GeroScience, 2021)

Detection methods and characterization of bovine viral diarrhea virus in aborted fetuses and neonatal calves over a 22-year period - Maximiliano J. Spetter; Enrique L. Louge Uriarte; Joaquín I. Armendano; Eleonora L. Morrell; Germán J. Cantón; Andrea E. Verna; Matías A. Dorsch; Susana B. Pereyra; Anselmo C. Odeón; Jeremiah T. Saliki; Erika A. González Altamiranda (Brazilian Journal of Microbiology, 2020)

Modification of plant cell wall chemistry impacts metabolome and microbiome composition in Populus PdKOR1 RNAi plants - Allison M. Veach; Daniel Yip; Nancy L. Engle; Zamin K. Yang; Amber Bible; Jennifer Morrell-Falvey; Timothy J. Tschaplinski; Udaya C. Kalluri; Christopher W. Schadt (Plant and Soil, 2018)

Entorhinal cortex volume is associated with episodic memory related brain activation in normal aging and amnesic mild cognitive impairment - Mehul A. Trivedi; Travis R. Stoub; Christopher M. Murphy; Sarah George; Leyla deToledo-Morrell; Raj C. Shah; Susan Whitfield-Gabrieli; John D. E. Gabrieli; Glenn T. Stebbins (Brain Imaging and Behavior, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Habitat use and activity patterns of urban-dwelling javelina - Cindy L. Ticer; Richard A. Ockenfels; James C. Devos; Thomas E. Morrell (Urban Ecosystems, 1998)